PENGUJIAN INOKULUM NASI BUBUK DI LAPANGAN - SASTRAATMADJA, DUDI D. (Research Center for Biology-Indonesian Institute of Sciences, 1987)
D.D. SASTRAATMADJA, 1987. Testing of rice meal inoculum in the fields Suppl.Berita Biologi 3:1-5.With the aim of testing and using of inoculum by users, studies of the using of inoculum rice powder for oncom production have been carried out.The experiment utilized different kinds of inoculum which contained some strains of Neurospora spp., Mucor spp.,and Rhizopus spp.have been done at several places of oncom producers in Bandung and Bogor.The quality of products were evaluated by analyzing of organoleptic test, texture and growth of mold comparing with local oncom. The results obtained in the experimentshowed that product made by using one strain of Neurospora spp., more liked moderately and having good mold growth, finely conpact and soft texture comparing with the other products and local red oncom in Bandung and Bogor.Besides that all of the strains of Mucur spp., produced good quality of oncom comparing with local black oncom.But all of the strains of Rhizopus spp., did not capable making good quality cf oncom. About the utilizingof powder inoculum by users in general must be fuether more investigated.